The role of aryl hydrocarbon receptor in the occurrence and development of periodontitis - Wu, Lingzhi; Li, Xiting; Li, Jinyu; Wang, Yan; Yang, Canyu; Zhao, Chuanjiang; Gao, Li (Frontiers in Immunology, 2024)
Periodontitis is a condition characterized by dysbiosis of microbiota and compromised host immunological responses, resulting in the degradation of periodontal tissues. The aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor, plays a crucial role in the pathogenesis of periodontitis. AHR serves as a pivotal mediator for the adverse impacts of exogenous pollutants on oral health. Research indicates elevated expression of AHR in individuals with periodontitis compared to those without the condition. However, subsequent to the identification of endogenous AHR ligands, researches have elucidated numerous significant advantageous roles associated with AHR activation in bone, immune, and epithelial cells. This review concentrates on the modulation of the AHR pathway and the intricate functions that AHR plays in periodontitis. It discusses the characteristics of AHR ligands, detailing the established physiological functions in maintaining alveolar bone equilibrium, regulating immunity, facilitating interactions between the oral microbiome and host, and providing protection to epithelial tissues, while also exploring its potential roles in systemic disorders related to periodontitis.